C9orf72 expansions are the most common cause of genetic frontotemporal dementia in a Southeast Asian cohort - Tan, Yi Jayne (2023)
Objective: Frontotemporal dementia (FTD) encompasses a spectrum of neurodegenerative disorders, including behavioural variant FTD (bvFTD), semantic variant primary progressive aphasia (svPPA) and non-fluent variant PPA (nfvPPA). While a strong genetic component is implicated in FTD, genetic FTD in Asia is less frequently reported. We aimed to investigate the frequency of Southeast Asian FTD patients harbouring known genetic FTD variants. Methods: A total of 60 FTD-spectrum patients (25 familial and 35 sporadic) from Singapore and the Philippines were included. All underwent next-generation sequencing and repeat-primed PCR for C9orf72 expansion testing. Neurofilament light chain (NfL) levels were measured in a subset of patients. Results: Overall, 26.6% (16/60 cases) carried pathogenic or likely pathogenic variants in a FTD-related gene, including: MAPT Gln351Arg (n = 1); GRN Cys92Ter (n = 1), Ser301Ter (n = 2), c.462 + 1G > C (n = 1); C9orf72 expansion (35–70 repeats; n = 8); TREM2 Arg47Cys (n = 1); and OPTN frameshift insertion (n = 2). Genetic mutations accounted for 48% (12/25) of patients with familial FTD, and 11.4% (4/35) of patients with sporadic FTD. C9orf72 repeat expansions were the most common genetic mutation (13.3%, 8/60), followed by GRN (6.7%, 4/60) variants. Within mutation carriers, plasma NfL was highest in a C9orf72 expansion carrier, and CSF NfL was highest in a GRN splice variant carrier. Interpretation: In our cohort, genetic mutations are present in one-quarter of FTD-spectrum cases, and up to half of those with family history. Our findings highlight the importance of wider implementation of genetic testing in FTD patients from Southeast Asia.